A apropriação do conceito numérico no 1º ano do ensino fundamental : um estudo na perspectiva da teoria histórico-cultural - Guillen, Juliane Dias (Universidade Federal de São Carlos, 2016)
This dissertation presents the master’s research developed at the Professional Graduate Program in Education of the Federal University of São Carlos, guided by the following question: how do students of the 1st grade of Elementary School take in the numerical concept while experiencing teaching activities? The objectives of this research were to identify how children from a class of the 1st grade of Elementary School take in the numerical concept, and to discuss it through the data obtained according to the cultural-historical activity theory. The methodology was based on a qualitative perspective, specifically on a case study of a class of six-year-old students from a municipal school in the state of São Paulo. Three teaching activities with an abacus were developed based on the cultural-historical perspective. Analysis was based on an interpretative view of the demonstrations expressed by the students during the development of the activities, transcribed through filming. The results show that during the realization of the situations triggering learning it was possible to perceive that the students appropriated the numerical concept.
Keywords: Atividade Orientadora de Ensino; Conceito Numérico; Ábaco; Guiding Teaching Activity; Numerical Concept; Abacus; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO